2022
DOI: 10.21062/mft.2022.052
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Usability of the Hybrid III Dummy for Crash Tests - Pilot Experiment

Abstract: The study is focused on the dynamic response of head and thoracic area of an anthropomorphic test device (ATD) during low-impact collisions with a tram. Two collision scenarios were analysed: the frontal impact (a chest as a primary contact area) and side impact (a thigh as a primary contact area). The measurements used a pedestrian dummy (Hybrid III 50 th percentile male dummy, Jasti Co., ltd., Tokyo, Japan) and a unique pendulum impact testing machine (impactor) of own design. The crash tests were conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…A real-life case with detailed crash information and medical damage reports that meets the requirements of crash reconstruction cannot be found, and because real-life crash tests are not morally and ethically permissible, this paper verifies the dynamics and kinematics behavior of the developed tram-pedestrian collision model through tramdummy impact tests. As shown in Figure 3, a Hybrid III 50th male pedestrian model provided by HNSAF was used to represent the pedestrian, which has been validated for use in tram-pedestrian crash tests [19,20]. Two real-world full-scale tram-dummy impact tests were conducted in 2023 at CRRC Qingdao Sifang Co., Ltd., Qingdao, China.…”
Section: Validation Of the Coupled Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…A real-life case with detailed crash information and medical damage reports that meets the requirements of crash reconstruction cannot be found, and because real-life crash tests are not morally and ethically permissible, this paper verifies the dynamics and kinematics behavior of the developed tram-pedestrian collision model through tramdummy impact tests. As shown in Figure 3, a Hybrid III 50th male pedestrian model provided by HNSAF was used to represent the pedestrian, which has been validated for use in tram-pedestrian crash tests [19,20]. Two real-world full-scale tram-dummy impact tests were conducted in 2023 at CRRC Qingdao Sifang Co., Ltd., Qingdao, China.…”
Section: Validation Of the Coupled Modelmentioning
confidence: 99%
“…The study revealed that the pedestrian's size, the phase of the gait cycle, and the collision position significantly affected both the overall motion and the sustained injuries. In terms of real-world collision tests, Tomsovsky et al [19,20] validated the usability of the Hybrid III dummy for tram-pedestrian crash tests and analyzed the kinematics of tram-pedestrian collisions in the case of a side impact at a speed of 10 km/h. Fanta et al [21] carried out kinematic and HIC analysis of a pedestrian dummy collision with a KT8D5-type tram at speeds of 10 and 20 km/h.…”
Section: Introductionmentioning
confidence: 99%